Snake venom phospholipase A(2) inhibitors: Medicinal chemistry and therapeutic potential - Marcussi, Silvana; Oliveira, Clayton Z.; Sant'Ana, Carolina D.; Quintero, Aristides; Menaldo, Danilo L.; Beleboni, Rene O.; Stabeli, Rodrigo G.; Giglio, Jose R.; Fontes, Marcos R. M.; Soares, Andreimar M. (Bentham Science Publ Ltd, 2007)
Phospholipases A(2) (PLA(2)s) are commonly found in snake venoms from Viperidae, Hydrophidae and Elaphidae families and have been extensively studied due to their pharmacological and physiopathological effects in living organisms. This article reports a review on natural and artificial inhibitors of enzymatic, toxic and pharmacological effects induced by snake venom PLA(2)s. These inhibitors act on PLA(2)S through different mechanisms, most of them still not completely understood, including binding to specific domains, denaturation, modification of specific amino acid residues and others. Several substances have been evaluated regarding their effects against snake venoms and isolated toxins, including plant extracts and compounds from marine animals, mammals and snakes serum plasma, in addition to poly or monoclonal antibodies and several synthetic molecules. Research involving these inhibitors may be useful to understand the mechanism of action of PLA(2)s and their role in envenomations caused by snake bite. Furthermore, the biotechnological potential of PLA(2) inhibitors may provide therapeutic molecular models with antiophidian activity to supplement the conventional serum therapy against these multifunctional enzymes.
Keywords: phospholipases A(2); phospholipase A(2) inhibitors; natural and artificial inhibitors; snake venoms